Switching of Giant Lateral Force on Sub‐10 nm Particle Using Phase‐Change Nanoantenna (Adv. Theory Simul. 2/2018). Issue 2 (20th February 2018) - Cao, Tun; Bao, Jiaxin; Mao, Libang
Abstract : In article number1700027, Tun Cao and co‐workers obtain a giant lateral optical force (LOF) acting on sub‐10 nm particles using Fano resonance (FR). This FR is excited by an asymmetric plasmonic bowtie nanoantenna array, which is based on a Au/Ge2 Sb2 Te5 /Au trilayer. The direction of LOF is reversibly switched with the phase transition of Ge2 Sb2 Te5, which pushes the nanoparticle sideways in the opposite direction.